Soft System Methodology (SSM) Dalam Menganalisa Strategi Dan Inovasi Perusahaan Real Estat Developer Untuk Menghadapi Perubahan Tren Pada Pusat Perbelanjaan - Ferry Oktavian; Retno Kusumastuti Harjono; Rachma Fitriati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Shopping Centres are currently facing several problems in connection with the changing trends in their tenants, including anchor tenants who are radically changing and transforming. This research combines a qualitative - constructive approach with the Soft System Model (SSM) method. This choice is based on the ability of the SSM method to help researchers find and understand actual problems related to strategy modelling and innovation.. The trends experienced by real estate - retail business players in 2024 present challenges and opportunities for Developers and Shopping Centre Managers. By understanding these trends and adapting to the evolving market, they can position themselves for success in a competitive and dynamic retail landscape. Developers can focus on three strategic priorities: Reshaping the role of Shopping Centres to serve multiple purposes, Driving greater adjustments in tenancy mix, Developing new leasing models that capture the value derived from new business models.